Modular neuropile organization in the Drosophila larval brain facilitates identification and mapping of central neurons. - Iyengar, B.G.; Chou, C.J.; Sharma, A.; Atwood, H.L. (Journal of Comparative Neurology, 2006)
Elucidating how neuronal networks process information requires identification of critical individual neurons and their connectivity patterns. For this purpose, we used the third-instar Drosophila larval brain and applied reverse-genetic tools, immunolabeling procedures, and 3D digital reconstruction software. Consistent topological definition of neuropile compartments in the larval brain can be obtained through simple fluorescence-immunolabeling methods. The modular neuropiles can be used as a fiducial framework for mapping the projection patterns of individual neurons labeled with green fluorescent protein (GFP). GFP-labeled neurons often exhibit dendrite-like arbors as well as clustered varicose terminals on neurite branches that innervate identifiable neuropile compartments. We identified candidate cholinergic interneurons in genetic mosaic brains that overlap with the larval optic nerve terminus. By using the neuropile framework, we demonstrate that the candidate visual interneurons are not a subset of the previously identified circadian pacemaker neurons that also contact the larval optic nerve terminus; they may represent parallel pathways in the processing of visual inputs. Thus, in the Drosophila larval brain, modular neuropiles can be used as a framework for systematically identifying, mapping, and classifying interneurons; understanding their roles in behavior can then be pursued further.